Sosialisasi Dan Pelatihan Cara Beternak Kelinci Bagi Peternak Kelinci Di Kabupaten Soppeng - Utami, Sri Wira; Sonjaya, Herry; Tullah, Muh. Firdaus; Irwan, Irwan; Aksan, Muhammad; R, Muh. Faisal Rahmat (Pakis Journal Institute, 2024)
Rabbits are livestock that are easy to breed in Indonesia. Rabbits are one of the sources of livelihood for the